La irregularidad en los juzgados de trabajo del cantón Machala respecto al procedimiento de los juicios laborales. - Espinoza Dávila, Rosa Margarita (2015)
This research has the problem if there enough existing laws in the organic code of judicial function, performance adopting judicial officials in the absence of application of constitutional principles of speed and procedural economy.